Biochemical and Clinical Evaluation of Novel Tyrosine Kinase Inhibitors in Breast Cancer: Molecular Docking and Biomarker Correlation Study - Wijdan Abdullameer Kamel (International Journal of Scientific Research and Innovative Studies, 2026)
The research assesses four new chemical substances which are Compound A through D which consist of quinazoline and pyrimidine and indole and quinoline derivatives for their ability to function as tyrosine kinase blockers in breast cancer treatment using molecular docking methods and laboratory tests. The molecular docking study which utilized AutoDock Vina demonstrated that Compound A which is a quinazoline derivative showed the highest binding affinity for EGFR at -10.34 kcal/mol and HER2 at -9.12 kcal/mol when compared to erlotinib and gefitinib. The in vitro MTT assays showed that Compound A had greater potency with IC50 values of 0.012 µM for MCF-7 and 0.034 µM for MDA-MB-231 which represented 7-fold and 4.5-fold increases above erlotinib. The Western blot analysis showed that p-EGFR and p-HER2 and downstream AKT/ERK1/2 signalling experienced major reductions. The study showed that Compound A caused apoptosis in 57.2% of MCF-7 cells and 53.8% of MDA-MB-231 cells which exceeded the erlotinib apoptosis rates. The ADMET profiling results showed that the drug exhibited good pharmacokinetic characteristics. The study found that Compound A's effectiveness depends on the EGFR and HER2 expression levels which were observed together with Ki-67 and Bax and Bcl-2 alterations thus confirming its value as a preclinical candidate for targeted breast cancer treatment. Keywords: Breast cancer; Tyrosine kinase inhibitors; Molecular docking; EGFR; HER2 Received Date: February 22, 2026 Accepted Date: March 14, 2026 Published Date: April 02, 2026 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/653